2020
DOI: 10.2196/15337
|View full text |Cite
|
Sign up to set email alerts
|

Usability Evaluations of Mobile Mental Health Technologies: Systematic Review

Abstract: Background Many mobile health (mHealth) apps for mental health have been made available in recent years. Although there is reason to be optimistic about their effect on improving health and increasing access to care, there is a call for more knowledge concerning how mHealth apps are used in practice. Objective This study aimed to review the literature on how usability is being addressed and measured in mHealth interventions for mental health problems. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 75 publications
(264 reference statements)
0
61
0
Order By: Relevance
“…Half of the reviews included in this scoping review did not refer to the characteristics of the participants included in the primary studies reviewed. Of the reviews, 50% (10/20) reviews that reported on any of the participants' characteristics, 4 reported mean age or age range [ 36 , 41 , 46 , 49 ], 4 reported the gender of participants [ 36 , 41 , 44 , 46 ], 8 reported the sample size [ 35 , 36 , 39 , 41 , 42 , 46 , 47 , 49 ], and 7 reported on other characteristics of participants by describing them as healthy participants or as having a specific clinical condition [ 36 , 37 , 39 , 41 , 44 , 46 , 49 ]. Nevertheless, 20% (4/20) reviews that reported the age of the participants also reported that not all primary studies detailed such information.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Half of the reviews included in this scoping review did not refer to the characteristics of the participants included in the primary studies reviewed. Of the reviews, 50% (10/20) reviews that reported on any of the participants' characteristics, 4 reported mean age or age range [ 36 , 41 , 46 , 49 ], 4 reported the gender of participants [ 36 , 41 , 44 , 46 ], 8 reported the sample size [ 35 , 36 , 39 , 41 , 42 , 46 , 47 , 49 ], and 7 reported on other characteristics of participants by describing them as healthy participants or as having a specific clinical condition [ 36 , 37 , 39 , 41 , 44 , 46 , 49 ]. Nevertheless, 20% (4/20) reviews that reported the age of the participants also reported that not all primary studies detailed such information.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 20 systematic reviews included, only 3 (15%) [ 33 , 40 , 41 ] did not refer to the methods and techniques of usability used. Among the inquiry methods, the questionnaires/scales (15/20, 75%) and interviews (12/20, 60%) were most commonly reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many have been incorporated into selfhealth programs and are most often used alone, but sometimes with other people. Apart from studies of usability, there have been few controlled studies of their clinical benefits, and a majority have been of very short duration and involved younger and mixed age samples (Aref-Adib et al, 2019;Inal et al, 2020;Rathbone and Prescott, 2017). Rathbone and Prescott's (2017) review found only four studies of persons with schizophrenia; a more recent review by Aref-Adib et al (2019) identified 26 studies using digital interventions that included persons with bipolar illness or schizophrenia.…”
mentioning
confidence: 99%